2000
DOI: 10.1209/epl/i2000-00339-6
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effect of Co diffusion in thin amorphous Co 51 Zr 49 layers during structural relaxation

Abstract: The time dependence and the isotope effect E = (Dα/D β − 1)/( m β /mα − 1) of Co diffusion have been measured in amorphous Co51Zr49 during structural relaxation. The radiotracer technique in conjunction with serial sectioning using ion-beam sputtering was employed to observe diffusion on a nanometer scale. A drastic drop of diffusivity during structural relaxation in these thin films was found which is of the same order of magnitude observed in much thicker Co89Zr11 glasses (Dörner W. and Mehrer H., Phys. Rev.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…43 These studies again support a collective mechanism for atomic diffusion in amorphous alloys. The present results, while in agreement with these earlier findings, 40,41,43 provide a deeper insight into the mechanism of diffusion in the unrelaxed state: we find that although the mechanism of diffusion involves a collective jump of a group of atoms in both unrelaxed and relaxed amorphous states, the average number of atoms participating in a diffusive jump exhibits variation in different regimes. In the lower-temperature range, where the quenched-in excess free volume is still not annihilated out, the average number of atoms participating in a diffusive jump is only 6, as compared to 22 in the relaxed state.…”
Section: Discussionsupporting
confidence: 93%
“…43 These studies again support a collective mechanism for atomic diffusion in amorphous alloys. The present results, while in agreement with these earlier findings, 40,41,43 provide a deeper insight into the mechanism of diffusion in the unrelaxed state: we find that although the mechanism of diffusion involves a collective jump of a group of atoms in both unrelaxed and relaxed amorphous states, the average number of atoms participating in a diffusive jump exhibits variation in different regimes. In the lower-temperature range, where the quenched-in excess free volume is still not annihilated out, the average number of atoms participating in a diffusive jump is only 6, as compared to 22 in the relaxed state.…”
Section: Discussionsupporting
confidence: 93%
“…The vanishing isotope effect in the as-quenched state will be discussed elsewhere in connection with other results on the time dependence of diffusivity and isotope effect during structural relaxation and on the effect of quenched in-excess volume on diffusion [42]. Here we note only that, different from earlier results [43] in a metalmetalloid glass, we have no indications of single-atom jumps in the as-quenched state.…”
Section: Evidence Of Highly Collective Co Diffusion In the Whole Stabsupporting
confidence: 44%
“…The authors attributed this to the fact that the evaporation produced well relaxed samples. Furthermore, Faupel et al, 39,40 found a significant isotope effect in the diffusivity of Co in melt-spun amorphous Co 76.7 Fe 2 Nb 14.3 B 7 while in sputter deposited amorphous Co 51 Zr 49 no isotope effect was observed. This difference was again attributed to a difference in the structure of as prepared melt-spun and sputter deposited amorphous alloy.…”
Section: Figmentioning
confidence: 95%